Irish stereotype in American cinema : stories of violence - Szczypa, Piotr (Brill, 2021)
"Discussing the role of violence in the Irish stereotype, this book is a fascinating story of the changing perception of the Irish in America as told by American cinema. From Levi and Cohen, Irish Comedians (1903) to The Irishman (2019), some of the productions analyzed here are timeless classics; others have almost been forgotten. What they have in common is the presence of violence as the key ingredient in the construction of Irish characters. In his insightful study, Piotr Szczypa employs imagological perspective to investigate the evolution of their portrayal in American films, showing not only how the Irish have adjusted to America but also how America has embraced Irishness"-- Provided by publisher.
Keywords: Irish in motion pictures.; Irish Americans in motion pictures.; Violence in motion pictures.; Stereotypes (Social psychology) in motion pictures.; Motion pictures -- United States -- History.; Irlandais au cinéma.; Américains d'origine irlandaise au cinéma.; Violence au cinéma.; Stéréotypes au cinéma.; Cinéma -- États-Unis -- Histoire.; Irish Americans in motion pictures; Irish in motion pictures; Motion pictures; Stereotypes (Social psychology) in motion pictures; Violence in motion pictures; United States; History